Cognitive performance and mental health in Long COVID patients: a cross-sectional study - Gómez Bravo, Raquel; Gebhardt, Charlotte Léonie; Infanti, Alexandre; Billieux, Joël; Ritzen, Mark; Moritz, Steffen; Benoy, Charles; Vögele, Claus (Verhaltenstherapie, 2025)
Introduction: Long COVID (LC) is characterized by enduring impairments in cognitive functions and increased stress, anxiety, and depression, lasting for more than 2 months. We investigated the extent of these impairments and their interrelation in individuals with self-reported LC compared to a non-LC control group. Methods: A cross-sectional online survey was conducted from September 2020 to December 2022, involving participants from the general population. The survey, in German and French, included the Verbal Learning and Memory Test and the Go/No-Go task to behaviorally assess cognitive functions and questionnaires for depression, anxiety, fatigue, and stress. A total of 1,218 individuals with LC and 314 controls completed the study, with case-control matching applied for comparisons between individuals of a similar age. Results: Verbal memory retention, as well as attentional and inhibitory control, were significantly lower in LC compared to controls. LC reported higher levels of depression, anxiety, fatigue, and stress. Behaviorally assessed cognitive impairments correlated with psychological distress. In the LC group, levels of self-reported cognitive difficulties were higher, and the correlation with cognitive performance test results was weaker, compared with controls. Conclusions: LC is associated with significant cognitive impairments and psychological distress that are intercorrelated. This underlines the need for targeted interventions to address the multifaceted consequences of LC.